Multi-Stage Partial Parallel Interference Cancellation Algorithm for MUSA Systems - Yan Liang; Han Wu; Guangyu Wang (Universitas Ahmad Dahlan, 2016)
Multi-User Shared Access is a non-orthogonal multiple access scheme of 5G,which has a high computational complexity and a large time delay due to the usage of successive interference cancellation detection algorithm. This paper proposes a multi-stage partial parallel interference cancellation detection algorithm, which does not require repeated ordering and repeated matrix inversion. In the first stage of detection, the bits of these users with good channel conditions will be outputted, and the influence of multiple access interference on users with bad channel conditions in the second stage will be decreased. Theoretical analysis and simulation results show that the symbol error rate of the proposed algorithm is slightly better than that of the two-stage MMSE-PIC, and the complexity is reduced. In the meanwhile, the computational complexity is significantly reduced without SER performance degradation when compared with MMSE-SIC algorithm.